Evaluate the Effectiveness of Promotions in Optimizing Purchase Decisions - Sakti, B. Retno Pratiwi (Sapta Arga Nusantara, 2024)
This research aims to determine the effectiveness of promotions on purchasing decisions at PT Jaga Inti Boga in Jakarta. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research showed that the promotion variable obtained an average score of 3.41 with good criteria. The purchasing decision variable obtained an average score of 3.83 with good criteria. Promotion has a significant effect on purchasing decisions with the regression equation Y = 8.513 + 0.874X, and a correlation value of 0.784 or strong with a determination of 61.5%. The hypothesis test obtained t count > t table or (12.250 > 1.986) and was also strengthened with a significance of 0.000 < 0.05.